The association of serum 25-OH vitamin D with asthma in Saudi adults. Issue 36 (September 2018) - Al-Daghri, Nasser M.; Al-Attas, Omar S.; Yakout, Sobhy M.; Alnaami, Abdullah M.; Wani, Kaiser; Alokail, Majed S.
Abstract : Abstract: The study aimed to assess the differences and associations of serum 25 (OH)D levels in Saudi adults with and without asthma. A total of 1070 Saudi adults aged 22 to 28 years (359 with known asthma and 711 matched nonasthmatic controls) were selected randomly from the Riyadh Cohort, Saudi Arabia. Serum 25(OH)D serum levels were measured. Asthma diagnosis was taken from questionnaires. In all participants, 359 (33.6%) were known asthmatic and 711 (66.5%) were nonasthmatic. The overall incidence of vitamin D deficiency (serum 25(OH)D <25 nmol/L) was 29.6% in controls and 35.6% in asthma group ( P  = .01). The asthma group have a significantly lower serum 25(OH)D than the control group ( P  = .01) but lost significance after adjusting for age, body mass index (BMI), and sex. Nonasthmatic and asthmatic females had a higher incidence of vitamin D deficiency (33% and 46%) than nonasthmatic and asthmatic males (17% and 33%). Vitamin D deficiency is significantly high among Saudi adults with asthma, but more so among women. Whether vitamin D deficiency exacerbates asthma attack remains to be proven in this population.